2017
DOI: 10.4236/ampc.2017.78024
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Treatment Methods for a PEDOT:PSS Transparent Conductive Film Produced Using an Inkjet Method

Abstract: Flexible devices manufactured using printed electronics have attracted the attention of many researchers. A high-performance transparent conductive film exhibiting high flexibility and elasticity is expected to be developed because of its need for the creation of flexible devices. An indium tin oxide (ITO) thin film, which has generally been used, has weaknesses such as fragility to bending stress and depletion of the resource. This study focused on poly (3, 4-ethylenedioxythiophene)/poly (styrenesulfonate) (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Several methods have been proposed to enhance electronic and morphological characteristics of PEDOT:PSS films via solvent post-treatments [7,28,29] in order to improve FF, parasitic resistances, and performance characteristics in organic solar cells. Following these approaches, we have demonstrated that the same idea can be used to control PEDOT:PSS film characteristics for application in hybrid PEDOT:PSS/a-SI:H interfaces [23]: an improvement of conductivity can be obtained in PEDOT:PSS films via IPA post-treatments; thus, to better understand and control PEDOT:PSS film characteristics for hybrid PEDOT:PSS/buffer/a-Si:H heterojunctions, the effects of three different IPA post-treatment techniques on the electrical, optical, and morphological characteristics of PEDOT:PSS films are studied.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods have been proposed to enhance electronic and morphological characteristics of PEDOT:PSS films via solvent post-treatments [7,28,29] in order to improve FF, parasitic resistances, and performance characteristics in organic solar cells. Following these approaches, we have demonstrated that the same idea can be used to control PEDOT:PSS film characteristics for application in hybrid PEDOT:PSS/a-SI:H interfaces [23]: an improvement of conductivity can be obtained in PEDOT:PSS films via IPA post-treatments; thus, to better understand and control PEDOT:PSS film characteristics for hybrid PEDOT:PSS/buffer/a-Si:H heterojunctions, the effects of three different IPA post-treatment techniques on the electrical, optical, and morphological characteristics of PEDOT:PSS films are studied.…”
Section: Resultsmentioning
confidence: 99%
“…The thin film was more uneven when the polar solvent was applied. It has been reported that the electrical and optical properties improve if the surface roughness is reduced [23]. However, we were able to prevent the resistivity from increasing.…”
Section: Resultsmentioning
confidence: 61%
“…We produced a flexible transparent conductive film by applying the material onto a plastic substrate using an inkjet printer. The main challenges in producing the organic transparent conductive film using the inkjet printing method are homogeneity of the surface and improving the characteristics of the thin film [23]. If we can solve these issues and produce a practical transparent conductive film, it will become possible to manufacture flexible devices, including wiring and electrodes, using only printing technology.…”
mentioning
confidence: 99%
“…For this purpose, addition of organic compound, such as ethylene glycol (EG), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), ionic liquid or anionic surfactant is very beneficial and can enhance the conductivity by two or three orders of magnitude [11][12][13][14] . Enhancement in conductivity of the films, associated with morphological and compositional changes, such as grain growth, polymer chain expansion, phase separation and PSS removal, can also be achieved by post-deposition treatments with heat, salts, cosolvents and acids [15][16][17] . Recently reported results demonstrated that treatment with concentrated sulfuric acid can enhance the conductivity of PEDOT:PSS films to more than 4×10 3 S cm −1 17 .…”
Section: Introductionmentioning
confidence: 99%